Orphan train to cattle baron [large type] - Gunn, Johnny (Jack Slater, 2024)
"In the fall of 1872, following a buggy mishap that killed his parents, Jack Slater, ten years old, was flung to the streets of New York City, among thousands of misplaced, orphaned, or runaway children. He was saved by the Children's Aid Society that placed orphaned children with families on the frontier. These families welcomed the children and most found loving homes. Some grew up to become industrial, political, or community leaders. Slater did not find a loving home. Instead, he found himself at Pete Jablonski's farm in Fargo, Dakota Territory where abuse was a daily dose of reality. When outlaws rob a local mine payroll and kill four men in the process, Slater makes a mortal enemy of the Elko County Sheriff that takes Slater's life is an unexpected direction."--